National Accounts Statistics: Analysis of Main Aggregates 2004-2005 - United Nations Department of Economic; Social Affairs (United Nations, 2007)
This publication contains detailed national accounts estimates for some 207 countries and areas of the world for the years 1970 to 2004/2005. The national data for each country and area are presented in separate chapters using uniform table headings and classifications recommended in the United Nations System of National Accounts 1993. Statistics on national accounts aggregates such as gross domestic product, per capita gross domestic product, shares of gross domestic product by expenditure and by kind of activity, average growth of gross domestic product and components thereof, and implicit price deflators are included.